ZAGREB BREWERY: THE GENESIS OF CONSTRUCTION FROM ITS FOUNDING IN 1892 TO THE PRESENT DAY - Vedran Ivanković (e-Zbornik. Elektronički Zbornik Radova Građevinskog Fakulteta)
The Zagreb Brewery was founded in 1892 in Gornja Ilica (today Ilica No. 224) as the Zagreb Joint Stock Brewery and Malt Factory JSC. It is one of the rare industrial plants that has operated on the same location since its foundation. It was planned as a production complex of 11 buildings that were built and expanded until the First World War, namely: 1892–1897 according to the designs of Kuna Waidmann, then 1897–1912 according to the designs of Martin Pilar, and immediately before the First World War according to the designs of the construction company "Pollak, Albert and Bornstein" (after the First World War "Pollak and Bornstein"). As a representative production complex built in the historicist (neo-Renaissance) style, it marked the western part of Ilica, introducing the first public (entertainment) content to the former periphery. After privatization in 1994, the first and most valuable building layer was devastated beyond recognition by additions, and the devastation began to a lesser extent after the Second World War. Today, the Zagreb Brewery is a protected cultural property, but there are no plans yet for its restoration.